PI/backstepping control of snake robot optimazed by genetic algorithm - Jafari, Maryam; Shahmansoorian, Aref (International Journal of Engineering and Technology, 2014)
This paper describes the design of robust control of PI/Backstepping for the snake robot to control the joints motion. First, the stability of the method is proved and, by applying this controller to the robot, its motion pattern is controlled in a way that it can move and follow by mimicking the motion of real snakes on the predefined trajectories. Then, the control parameters are optimized using the Genetic Algorithm (GA). Comparing obtained results with sliding mode revealed that, the former has significantly reduced the tracking error and control energy; in addition there is no chattering phenomenon.   Keywords: Snake Robot, PI/Backstepping Control, Genetic Algorithm, Control Energy.